Number and orientation of fault sets in the field and in experiments - Aydin, Atilla; Reches, Ze'ev (Geological Society of America, 1982)
Arrays of faults that can be grouped into multiple sets occur in the Entrada and Navajo Sandstones in southeastern Utah. The faults form a network that usually has a rhombohedral pattern both in map and cross-sectional views. Similar fault patterns were formed experimentally in cubic samples of sandstone, limestone, and granite deformed to failure with a polyaxial apparatus. The faulting theory of Anderson fails to explain both the number and the orientation of the faults observed in this study. However, the number and orientation of faults can be understood in terms of a theory of deformation of rock solely by slip along planes.